Dynamic Response Analysis of the Aircraft Exposed to the Lateral Travelling Gust. Issue 1 (1st November 2022) - Jing, Zhiwei; Tang, Chu
Abstract: The travelling gust from detonation is an interesting and severe excitation for a flying aircraft, and it is characterized by high emanating speed and takes strong energy. Previous investigations on the dynamic response characteristics of the aircraft in the tail-on or head-on travelling gust have been carried out. This paper focuses on the lateral travelling gust and its influence on the dynamic response of the aircraft. Based on conventional flight dynamics equations, the dynamics modelling and simulation technique of the rigid aircraft exposed to the lateral travelling gust is established. By employing the static pressure distributions, one quasi-steady aerodynamics computation method is presented to determine the aerodynamic force and moment on the aircraft in the travelling gust. Simulation results show that the approach presented in this paper is effective and can deal with the engineering requirement. Results also indicate that the enveloping process of the travelling gust increases the aerodynamic moment of the x -axis significantly and subsequently influences the dynamic responses along the x -axis.